Preservation of vision by transpalpebral electrical stimulation in mice with inherited retinal degeneration - Gunes, Kasim; Chang, Karen; Lennikov, Anton; Tai, Wai Lydia; Chen, Julie; ElZaridi, Farris; Cho, Kin-Sang; Utheim, Tor Paaske; Dong Feng, Chen (Frontiers in Cell and Developmental Biology, 2024)
The potential neuroprotective and regenerative properties of electrical stimulation (ES) were studied in rhodopsin knockout mice (Rho -/-), a murine model of inherited retinal degeneration. The study focused on assessing the impact of varying ES frequencies on visual functions and photoreceptor cell survival in Rho -/-mice. To elucidate the impact of electrical stimulation on cone survival, Rho -/-mice received either sham or transpalpebral ES using biphasic ramp or rectangular waveforms at 100 µA amplitude, starting at six weeks of age. The treatment duration spanned from one to three weeks. The optimal treatment frequency of ES sessions was determined by applying ES every one, two, or three days in three separate groups of Rho -/-mice. The sham group received daily treatments without the application of ES. Our study revealed significant improvement of visual function in Rho -/-mice following daily or every-other-day noninvasive transpalpebral ES, as evidenced by electroretinogram and optomotor response-based visual behavior assays. Concurrently, assessment of outer nuclear thickness and immunohistochemistry for the cone photoreceptor cell marker PNA demonstrated pronounced increases in the survival of rods and cones and improvement in the morphology of the inner and outer segments. This study underscores the protective effect of non-invasive ES in rhodopsin knockout-induced retinal degenerative disorders, providing a foundation for developing targeted therapeutic interventions for retinitis pigmentosa.